Ancient dog mitogenomes support the dual dispersal of dogs and agriculture into South America - Manin, Aurelie; Debruyne, Regis; Lin, Audrey; Lebrasseur, Ophelie; Dimopoulos, Evangelos Antonios; Gonzalez Venanzi, Lucio; Charlton, Sophy; Scarsbrook, Lachie; Hogan, Andrew; Linderholm, Anna; Boyko, Adam R.; Joncour, Pauline; et al. (My University, 2025)
Archaeological and palaeogenomic data show that dogs were the only domestic animals introduced during the early peopling of the Americas. Hunter-gatherer groups spread quickly towards the south of the continent, but it is unclear when dogs reached Central and South America. To address this issue, we generated and analysed 70 complete mitochondrial genomes from archaeological and modern dogs ranging from Central Mexico to Central Chile and Argentina, revealing the dynamics of dog populations. Our results demonstrate that pre-contact Central and South American dogs are all assigned to a specific clade that diverged after dogs entered North America. Specifically, the divergence time between North, Central and South American dog clades is consistent with the spread of agriculture and the adoption of maize in South America between 7000 and 5000 years ago. An isolation-by-distance best characterizes how dogs expanded into South America. We identify the arrival of new lineages of dogs in post-contact South America, likely of European origin, and their legacy in modern village dogs. Interestingly, the pre-contact Mesoamerican maternal origin of the Chihuahua has persisted in some modern individuals.
Keywords: palaeogenomics; phylogeography; animal domestication; migration; archaeology; americas